Detection of Lymphocytic Choriomeningitis Virus Antibody in Murine Sera by Immunofluorescence - Lewis, Vester (1969)
An immunofluorescence technique developed for detection of antibody in murine sera to lymphocyitc choriomeningitis virus is described.